Why do enterprise risk management systems fail? Evidence from a case study of AIG. (1st January 2013) - Pathak, Jagdish; Karim, Khondkar E.; Carter, Clairmont; Xie, Yingshu
In this paper we use the enterprise risk management (ERM) framework as proposed by the COSO to analyse eight components of the American International Group's (AIG) risk management system, and then study how such a poor risk management system led to AIG's liquidity crisis. We address two research questions in this paper: First, we examine the direct reasons for AIG's liquidity risk in September 2008. Second, we conduct a qualitative case study to analyse how the limitations of AIG's enterprise-wide risk management system led to its liquidity crisis. We identify that issuing credit default swaps (CDSs) and investing in residential mortgage backed securities (RMBS) and commercial mortgage backed securities (CMBS) were the direct causes of AIG's liquidity crisis. However, the fundamental reason was AIG's poor risk management system. Our field case study is consistent with the Erickson et al. (2000, pp.165–194) research design of first-hand and second-hand evidence for drawing inferences, and follows the prescriptions of Merchant and Van der Stede (2006, pp.117–134); and Ahrens and Chapman (2006, pp.819–841). We provide public policy and practical implications based on the conclusions of this case study.